PARG Protein Regulation Roles in Drosophila Longevity Control. - Bordet, G.; Tulin, A.V. (International journal of molecular sciences, 2024)
Aging, marked by a gradual decline in physiological function and heightened vulnerability to age-related diseases, remains a complex biological process with multifaceted regulatory mechanisms. Our study elucidates the critical role of poly(ADP-ribose) glycohydrolase (PARG), responsible for catabolizing poly(ADP-ribose) (pADPr) in the aging process by modulating the expression of age-related genes in Drosophila melanogaster. Specifically, we uncover the regulatory function of the uncharacterized PARG C-terminal domain in controlling PARG activity. Flies lacking this domain exhibit a significantly reduced lifespan compared to wild-type counterparts. Furthermore, we observe progressive dysregulation of age-related gene expression during aging, accelerated in the absence of PARG activity, culminating in a premature aging phenotype. Our findings reveal the critical involvement of the pADPr pathway as a key player in the aging process, highlighting its potential as a therapeutic target for mitigating age-related effects.